Understanding electric vehicle adoption: The role of information frictions and heterogeneous beliefs - Aoife Claire Fitzpatrick (Leibniz Institute for Financial Research SAFE, 2025)
In 2023, the transportation sector in Europe contributed 25% of CO2 emissions, with almost no reduction since 2010. Despite government policies promoting decarbonization, public adoption of electric vehicles (EVs) remains limited. This study, involving 5,500 German participants from a pre-registered survey and experiment, identifies information frictions and mixed beliefs about EV sustainability as key barriers. Two treatments-highlighting EVs' environmental benefits and public policies-both increased participants' likelihood of choosing an EV, but only the environmental treatment raised willingness to pay more. The findings underscore the need for clear, accurate information to complement policy efforts, reducing disinformation and amplifying the impact of initiatives to meet climate goals.
Keywords: D12; D91; G11; G18; G53; 330; Electric Vehicles; Consumer Behaviour; Behavioural Economics; GreenTransition